2009
DOI: 10.5380/rsa.v10i4.14800
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Do Ácido Giberélico Nas Características Ampelométricas Dos Cachos De Uva ‘A Dona’ E ‘Marte’

Abstract: Os experimentos foram realizados em videiras de ‘A Dona’ e ‘Marte’ em Jundiaí-SP, com o objetivo de avaliar o efeito do ácido giberélico (GA3) nas características morfológicas e químicas dos cachos e bagas de uva. Na cultivar A Dona enxertada sobre os porta-enxertos ‘IAC 766’ e Ripária do Traviú, avaliou-se o efeito do GA3 nas concentrações de 0, 10, 20 e 30 mg dm-3, aplicado aos 20 dias após o pleno florescimento. Na cultivar Marte avaliou-se o efeito do GA3 nas concentrações de 0, 15, 30, 45 e 60 mg dm-3. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
1
1
Order By: Relevance
“…Separate evaluation of the different rootstocks in each cultivar shows a significant effect of the rootstock on the cultivar A Dona only in the number of bunches per vine, in which IAC 572 (76.03 ± 4.06) was superior to SO4 (56.76 ± 10.85). Tecchio et al (2009) observed that A Dona grown on the rootstock IAC 766 in the state of São Paulo had greater bunch weight and berry size than those found in this study, which may be explained by the treatments with gibberellic acid. In contrast, results obtained in the same experimental area by Brito et al (2019) indicate similar values for berry weight, but lower values for bunch weight and titratable acidity than those observed in this study.…”
Section: Resultscontrasting
confidence: 58%
“…Separate evaluation of the different rootstocks in each cultivar shows a significant effect of the rootstock on the cultivar A Dona only in the number of bunches per vine, in which IAC 572 (76.03 ± 4.06) was superior to SO4 (56.76 ± 10.85). Tecchio et al (2009) observed that A Dona grown on the rootstock IAC 766 in the state of São Paulo had greater bunch weight and berry size than those found in this study, which may be explained by the treatments with gibberellic acid. In contrast, results obtained in the same experimental area by Brito et al (2019) indicate similar values for berry weight, but lower values for bunch weight and titratable acidity than those observed in this study.…”
Section: Resultscontrasting
confidence: 58%
“…The varieties Venus and Mars are American hybrids with early cycles (Camargo 1993;Botelho et al, 2002;Tecchio et al, 2009). Corroborating Borges et al, (2010) grouped into Semi-Arid Brazilian conditions the varieties, Flame Seedless and Fiesta, with 59% similarity in days to complete the cycle.…”
Section: Principal Component Analysis and Upgmamentioning
confidence: 99%
“…Exogenous applications of gibberellic acid suppress seminal phytohormone production activity (Tecchio et al, 2009), which is responsible for the formation and distribution of fruit composition through cell division and elongation (Taiz et al, 2017). Increasing concentrations of gibberellic acid result in seed atrophy, which have their functionality reduced by the presence of the synthetic hormone, which starts to play the role of the natural hormone (Pereira et al, 2014).…”
Section: Resultsmentioning
confidence: 99%